Altered Ground Reaction Force and Dynamic Stability During a Single-Leg Stabilization Task in Female Athletes With Lateral Ankle Sprain History and Dysfunctional Breathing Patterns. - Terada, Masafumi; Shimozawa, Yuka; Sugiyama, Takashi; Kusagawa, Yuki; Tanaka, Takahiro; Hori, Miyuki; Kurihara, Toshiyuki; Isaka, Tadao (Journal of Sport Rehabilitation, 2026)
Context: Female athletes frequently experience lateral ankle sprains (LAS) during unilateral jump-landing activities and face a significant risk of recurrent ankle injury. LAS has been associated with reduced diaphragm contractility and altered breathing mechanics. The diaphragm and breathing mechanics are crucial for mitigating landing impact, which is typically impaired in individuals with LAS. Given this connection, innovative rehabilitation approaches that address dysfunctional breathing mechanics may be warranted. To date, no research has investigated associations between breathing mechanics and landing kinetics in adolescent female athletes with LAS. This study aimed to compare ground reaction force (GRF) and dynamic stability during a single-leg stabilization task between female athletes with a history of LAS who exhibited diaphragmatic breathing patterns and those who had dysfunctional breathing patterns. Design: Case–control study. Methods: Two hundred eighty-three competitive female athletes with a previous history of LAS were recruited from middle school, high school, and Division I college teams. The Hi-Lo test was utilized to categorize participants as dysfunctional breathers or diaphragmatic breathers according to their breathing patterns. Each participant completed 3 trials of a single-leg drop-landing task. Normalized peak vertical and posterior GRF data were extracted, and the average loading rate was calculated from the normalized vertical GRF. The norm of the horizontal component of the GRF was used to calculate time to stabilization. Results: Forty female athletes with LAS history (14.1%) were classified as diaphragmatic breathers, and 243 (85.9%) were classified as dysfunctional breathers. Female athletes with LAS history who exhibited dysfunctional breathing patterns demonstrated a greater peak posterior GRF (P =.01) and longer time to stabilization (P =.04) compared with those who had diaphragmatic breathing patterns. Conclusions: Dysfunctional breathing patterns may contribute to decreased dynamic stability and force attenuation capabilities during single-leg landing tasks following LAS. Assessing the biomechanical dimension of breathing patterns may help clinicians identify patient-specific impairments in individuals with LAS, particularly those with deficits in dynamic postural stability and force attenuation.